2002
DOI: 10.1002/ijc.10080
|View full text |Cite
|
Sign up to set email alerts
|

Persistant human papillomavirus infection and smoking increase risk of failure of treatment of cervical intraepithelial neoplasia (CIN)

Abstract: Women with abnormal smears have an increased risk of developing cervical cancer. During the 8 years following conservative treatment of cervical intraepithelial neoplasia (CIN), their risk of invasive cervical cancer is about 5 times greater than that of the general population. Human papillomavirus (HPV) has been associated with the natural history of both CIN and cervical cancer. To date, there have been no published reports on the predictive value of HPV testing in the treatment outcome of CIN. A prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
6

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 32 publications
2
47
0
6
Order By: Relevance
“…Persistent post-treatment high-risk human papillomavirus (hr-HPV) is a risk factor for subsequent SIL [15,16]. A meta-analysis of Zielinski et al showed that the status of excision margins, posttreatment cytology, post-treatment hr-HPV or combinations had a negative predictive value of 91-99%, the positive predictive values of these parameters were 25-51% [17].…”
Section: Discussionmentioning
confidence: 99%
“…Persistent post-treatment high-risk human papillomavirus (hr-HPV) is a risk factor for subsequent SIL [15,16]. A meta-analysis of Zielinski et al showed that the status of excision margins, posttreatment cytology, post-treatment hr-HPV or combinations had a negative predictive value of 91-99%, the positive predictive values of these parameters were 25-51% [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, even women with clear margins following excision are at risk for disease recurrence (8). Carcinogenic human papillomavirus (HPV), the causative agent of cervical cancer and its precursor lesions, is present in up to one third of women following LEEP and is associated with disease recurrence (5,6,(9)(10)(11). Therefore, HPV testing may serve as a surveillance tool for identifying women at high risk of recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…In short-term follow-up, rates of recurrent/ residual CIN/VAIN 2þ ranged from 7% to 17.9%. [18][19][20][25][26][27] There are very few reports of long-term follow-up monitoring studies. In a large cohort of patients treated for CIN 3, Melnikow et al 5 reported a rate of recurrent/ residual CIN 2þ of 14%.…”
Section: Commentmentioning
confidence: 99%